2020
DOI: 10.3389/fmicb.2020.593472
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes for All

Abstract: Microbiome research projects are often interdisciplinary, involving fields such as microbiology, genetics, ecology, evolution, bioinformatics, and statistics. These research projects can be an excellent fit for undergraduate courses ranging from introductory biology labs to upper-level capstone courses. Microbiome research projects can attract the interest of students majoring in health and medical sciences, environmental sciences, and agriculture, and there are meaningful ties to real-world issues relating to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 98 publications
(103 reference statements)
1
4
0
Order By: Relevance
“…The idea of cross training between the disciplines of computer science and other fields such as food science may offer a partial solution to some of this by creating interactions between the 2 groups during classroom discussions ( Feye et al, 2020c ). This is also consistent with Muth and Caplan's (2020) observation that microbiome projects support development of critical thinking, problem solving, and collaboration skills which, in turn is more reflective of the changing requirements of the workforce. This holds true for food safety issues in the poultry food industries as well ( Dittmar et al, 2006 ; Ricke, 2015a ; Thompson et al, 2017 ).…”
Section: Educational Approaches For Communicating Microbiome Sequenci...supporting
confidence: 87%
See 2 more Smart Citations
“…The idea of cross training between the disciplines of computer science and other fields such as food science may offer a partial solution to some of this by creating interactions between the 2 groups during classroom discussions ( Feye et al, 2020c ). This is also consistent with Muth and Caplan's (2020) observation that microbiome projects support development of critical thinking, problem solving, and collaboration skills which, in turn is more reflective of the changing requirements of the workforce. This holds true for food safety issues in the poultry food industries as well ( Dittmar et al, 2006 ; Ricke, 2015a ; Thompson et al, 2017 ).…”
Section: Educational Approaches For Communicating Microbiome Sequenci...supporting
confidence: 87%
“…Increased efforts to develop educational materials and laboratory exercises for microbiome training at both the high school and college undergraduate level may change the level of familiarity with microbiome/bioinformatics in the next generation. Muth and Caplan (2020) summarized the efforts in different universities to develop microbiome research projects for undergraduates. Based on their surveys of biology faculty, they concluded that for some aspects such as quantitative and data processing, the lack of basic computing background in students, insufficient bioinformatic lesson plans, coupled with the rapidly changing bioinformatic program content were challenges along with limited faculty expertise and time.…”
Section: Educational Approaches For Communicating Microbiome Sequenci...mentioning
confidence: 99%
See 1 more Smart Citation
“…PARE provides an opportunity for scaffolding of different modules in different courses. In addition, it is complementary to other nationally-disseminated semester-long CUREs such as Tiny Earth/Small World Initiative ( Barral et al, 2014 , 2016 ; Hurley et al, 2020 ), SEA PHAGES ( Hatfull et al, 2006 ; Jordan et al, 2014 ), and Authentic Research Experience in Microbiology ( Muth and McEntee, 2014 ; Muth and Caplan, 2020 ). All are focused on some aspect of environmental microbiology, so together they provide ready-to-use options for scaffolding.…”
Section: Pare Is a Flexible And Inclusive Way To Engage Diverse Studementioning
confidence: 99%
“…The answer is no. It does not simply fit into any one of those boxes, but rather it is the nexus of those and several other fields, thereby making it a unique synthesis-an intricate composite of field, wet lab, theoretical, and computational work aimed at decoding microbial interactions with hosts and with each other [11,12]. Similarly, microbiome researchers often experience a limbo in expertise, relating to the Shakespearean phrase, "a jack of all trades, a master of none."…”
mentioning
confidence: 99%